Advances in brain inspired cognitive systems : 10th International Conference, BICS 2019, Guangzhou, China, July 13-14, 2019, proceedings / Jinchang Ren [and 7 more] (eds.) - Ren, Jinchang (Lecture notes in computer science, 2020)
This book constitutes the refereed proceedings of the 10th International Conference on Advances in Brain Inspired Cognitive Systems, BICS 2019, held in Guangzhou, China, in July 2019. The 57 papers presented in this volume were carefully reviewed and selected from 129 submissions. The papers are organized in topical sections named: neural computation; biologically inspired systems; image recognition: detection, tracking and classification; and data analysis and natural language processing. --